Neural soft computing based secured transmission of intraoral gingivitis image in e-health care - Arindam Sarkar; Joydeep Dey; Minakshi Chatterjee; Anirban Bhowmik; Sunil Karforma (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, a key based soft computing transmission of intraoral gingivitis image has been proposed without the exchange of common key in between the nodes. Gingivitis has been a type of periodontal disease caused due to bacterial colonization inside the mouth, having the early signs of gum bleeding and inflammations in human beings. In E-health care strata, online transmission of such intraoral images with secured encryption technique is needed. Session key based neural soft computing transmission by the dentists has been proposed in this paper with an eye to preserve patients’ confidentiality factor. To resist the data distortion by the eavesdroppers while on the transmission path, secured transmission in a group of tree parity machines was carried out. Topologically same tree parity machines with equal seed values were used by all users of that specified group. A common session key synchronization method was applied in that group. Intraoral image has been encrypted to generate multiple secret shares. Multiple secrets were transmitted to individual nodes in that group. The original gingivitis image can only be reconstructed upon the merging of threshold number of shares. Regression statistics along with ANOVA analysis were carried out on the result set obtained from the proposed technique. The outcomes of such tests were satisfactory for acceptance.